Penerapan Model Pembelajaran PBL Berbantuan Media Powerpoint untuk Meningkatkan Hasil Belajar pada Pembelajaran Tematik Kelas IV SDN 171 Rejang Lebong. - Asri Setya Ningrum; Herman Lusa; Hasnawati Hasnawati (Universitas Bengkulu, 2022)
This study aims to describe the application of the PBL model assisted by media powerpoint and improve student learning of thematic learning for class IV SDN 171 Rejang Lebong. This research is a Classroom Action Research. Subjects in the study were 18 students, with 9 males and 9 females. Data collection techniques using observation and test techniques. The research instrument was an observation sheet and a test sheet. The data analysis technique used qualitative and quantitative techniques. In the PBL model there is a syntax in the form of student orientation to problems, organizing students to learn, guiding individual/group experiences, developing and presenting work, analyzing and evaluating problem solving processes. In each syntax the teacher has implemented it well and there is an increase in student learning outcomes. In the cognitive aspect of the first cycle, Indonesian subjects obtained an average of 69.72 classical learning completeness of 61.11% and increased in the second cycle with an average of 77.5 classical learning completeness of 83.33%. Science subjects in the first cycle obtained an average of 67.77 with classical learning completeness 55.55%, increased in the second cycle with an average acquisition of 78.33 classical learning completeness 88.88%. The affective aspect of the first cycle obtained a class average of 4.91 with a sufficient category, increased in the second cycle by obtaining a class average of 5.88 in a good category. Psychomotor aspect in the first cycle the average grade obtained by 5 with enough categories, increased in the second cycle to obtain an average grade of 5.86 for both categories. Hence, the implementation of PBL model using powerpoint media enhanced the 4th grade students’ learning outcomes of SDN 171 Rejang Lebong.